2022
DOI: 10.1002/adem.202101134
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Polyurethane Tissue‐Engineering Scaffold with Hierarchical Microcellular Foam Structure and Antibacterial Properties

Abstract: This work proposes a facile fabrication strategy of polyurethane (TPU) tissue‐engineering scaffold with hierarchical structure, designed by combination of the fused deposition modeling (FDM) 3D printing and supercritical microcellular foaming by carbon dioxide (CO2). Further surface modification of TPU scaffold with graphene oxide (GO) was carried out by in situ polymerization of polydopamine (PDA) to ensure stable loading of GO with antibacterial properties. The influence of 3D‐printing temperature and speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…As shown in Figure 10, Li et al (2020) reported using polyetherimide and polylactic acid (PLA) filaments to manufacture hierarchical porous portions that were impregnated with CO 2 gas. Zhang et al (2022) offered a simple solution by combining 3D FFF printing with supercritical microcellular foaming to address the primary obstacle for tissue-engineering scaffolds with hierarchical topologies. As seen Figure 11 (Zhang et al, 2022), the flexibility of additive manufacturing design results in pores are larger than microns due to layer stacking, whereas microcellular structures result in pores smaller than microns due to foaming.…”
Section: In-situ Foam 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 10, Li et al (2020) reported using polyetherimide and polylactic acid (PLA) filaments to manufacture hierarchical porous portions that were impregnated with CO 2 gas. Zhang et al (2022) offered a simple solution by combining 3D FFF printing with supercritical microcellular foaming to address the primary obstacle for tissue-engineering scaffolds with hierarchical topologies. As seen Figure 11 (Zhang et al, 2022), the flexibility of additive manufacturing design results in pores are larger than microns due to layer stacking, whereas microcellular structures result in pores smaller than microns due to foaming.…”
Section: In-situ Foam 3d Printingmentioning
confidence: 99%
“…Zhang et al (2022) offered a simple solution by combining 3D FFF printing with supercritical microcellular foaming to address the primary obstacle for tissue-engineering scaffolds with hierarchical topologies. As seen Figure 11 (Zhang et al, 2022), the flexibility of additive manufacturing design results in pores are larger than microns due to layer stacking, whereas microcellular structures result in pores smaller than microns due to foaming. In-situ foam 3D printing requires an additional stage of gas impregnation before printing and the gas-saturated filaments commence to release gas as soon as they are removed from the high-pressure chamber, which is one of its biggest advantages.…”
Section: In-situ Foam 3d Printingmentioning
confidence: 99%
“…Overall, three approaches can be used to fabricate foamed parts in the material extrusion AM process: (a) prefoaming, (b) postfoaming, and (c) in situ foaming. In the prefoaming approach, the feedstock filament is usually foamed during filament fabrication and used as feedstock for 3D printing. The issue with this approach will be the lack of foaming control during the actual printing process, which limits the range of cellular structures that can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported CO 2 gas-impregnated polyetherimide and polylactic acid (PLA) filaments that were used to print foamed parts. Zhang et al also demonstrated the preparation of polyurethane foamed scaffolds using a similar approach . The cell nucleation, growth, and stabilization occurred as the CO 2 -saturated filament was heated during printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation